On Earth and as It Is in Heaven—There Is No Sex Trafficking in Heaven: A Qualitative Study Bringing Christian Church Leaders’ Anti-Trafficking Viewpoints to Trafficking Discourse - Knight, Logan (Religions, 2022)
There is a lack of contributions in sex trafficking the academic literature from Christian evangelical leaders despite their prominence in global counter-trafficking activism. Given that the academic literature influences professional and pedagogical discourse, the lack of evangelical Christian representation could diminish the complexity of trafficking discourses, limit balanced views of the flaws and strengths of evangelical counter-trafficking, and limit the opportunities for academia to understand and address problematic areas in evangelical counter-trafficking through an emic understanding of evangelical paradigms. Using a phenomenological lens to engage evangelical Christian pastors (n = 17) in the midwestern United States, this study examined the meaning faith leaders attach to counter-trafficking initiatives. Four themes emerged: (1) God cares about survivors of sex trafficking, giving Christians a moral obligation to intervene; (2) God, the Christian, and the survivor all have essential roles in tackling sex trafficking as part of helping humanity; (3) congregations’ faith-inspired but imperfect efforts to help an imperfect and complex world create many complexities; and (4) managing complexity involves applying the truths that underpin the Christian worldview, namely that God is good and people are valuable. These findings underscore the need to create an inclusive knowledge-producing forum that allows for a pragmatic exchange of ideas to expand the discourse between multiple counter trafficking actors.